Integrated approach for managing groundnut stem rot caused by Sclerotium rolfsii Sacc. - Deepika, B; Sheela, J; Indra, N; Kalaiyarasi, R; Navamaniraj, K N (Plant Science Today, 2025)
Groundnut (Arachis hypogaea L.), often referred to as the King of oil seeds, is a vital oil seed crop cultivated globally. However, its productivity is hampered by numerous abiotic and biotic stresses, with biotic stresses predominantly due to fungal and bacterial diseases. Among these, soil-borne fungal pathogens cause significant yield losses. Specifically, stem rot disease, caused by Sclerotium rolfsii Sacc., poses a substantial threat, leading to yield losses of up to 80%. This pathogen forms sclerotia, a resilient resting structure that can survive in the soil for many years and germinate under favorable environmental conditions. The persistence of sclerotia and the pathogen's broad host range make managing this disease particularly challenging through a single method. Effective management of stem rot disease necessitates an integrated disease management (IDM) approach, which combines cultural, chemical, and biological strategies. Cultural practices such as crop rotation, deep ploughing, and moisture regulation help to reduce inoculum levels in the soil. Chemical control involves the use of fungicides to reduce the pathogen load in the soil and protect the plants during vulnerable growth stages. Biological control employs antagonistic microorganisms that can inhibit the growth and activity of S. rolfsii. By integrating these diverse strategies, it is possible to effectively manage stem rot disease in groundnut, thereby enhancing productivity and sustainability in groundnut cultivation.